2012
DOI: 10.1002/ajh.23339
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of primary plasma cell leukemia identifies recurrent imbalances associated with changes in transcriptional profiles

Abstract: Primary plasma cell leukemia (pPCL) is a rare, yet aggressive form of de novo plasma cell tumor, distinct from secondary PCL (sPCL) which represents a leukemic transformation of pre-existing multiple myeloma (MM). Herein, we performed a comprehensive molecular analysis of a prospective series of pPCLs by means of FISH, single nucleotide polymorphism (SNP) array and gene expression profiling (GEP). IGH@ translocations were identified in 87% of pPCL cases, with prevalence of t(11;14) (40%) and t(14;16) (30.5%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 38 publications
1
59
0
5
Order By: Relevance
“…41 Others linked B55a to childhood teratoma, 42 prostate cancer, 43 colorectal cancer, 44 lung cancer, 45 and leukemia. 46 In this study we characterized B55a as a regulator of Plk1 and the DNA damage checkpoint, which finding may mechanistically explain how B55a functions as an important tumor suppressor. After all, it has been well established that dysregulation of Plk1 contributes to cancer progression and resistance, and the DNA damage checkpoint pathway constitutes an important anti-cancer barrier.…”
mentioning
confidence: 82%
“…41 Others linked B55a to childhood teratoma, 42 prostate cancer, 43 colorectal cancer, 44 lung cancer, 45 and leukemia. 46 In this study we characterized B55a as a regulator of Plk1 and the DNA damage checkpoint, which finding may mechanistically explain how B55a functions as an important tumor suppressor. After all, it has been well established that dysregulation of Plk1 contributes to cancer progression and resistance, and the DNA damage checkpoint pathway constitutes an important anti-cancer barrier.…”
mentioning
confidence: 82%
“…S5C and S5D). It is worth mentioning that none of the cytogenetic aberrations was associated per se with PFS and OS (15).…”
Section: Clinical Relevance Of Mirna Profiles In Ppclmentioning
confidence: 93%
“…All pPCL cases were investigated by fluorescence in-situ hybridization (FISH) for the major immunoglobulin heavy chain locus (IGH@) translocations and genetic lesions: results are reported in Table 1 and described extensively in ref. 15.…”
Section: Patient Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly purified (!90%) bone marrow PCs were obtained as previously reported (8). Demographic information and details on molecular alterations of the whole cohort were reported in a previous manuscript aimed at the genomic characterization of the samples (12). Fiftyfive newly diagnosed multiple myeloma patients were included in the study; these cases have been previously reported (13) and were selected on the basis of the representativeness of the main molecular characteristics.…”
Section: Patientsmentioning
confidence: 99%